PENGARUH KOMPETENSI, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN DI LINGKUNGAN PERGURUAN TINGGI (STUDI KASUS SEKOLAH TINGGI ILMU EKONOMI INDONESIA) - Farah Amanjaya, Nukie; Pragiwani, Meita (Jurnal Ekonomi Manajemen Bisnis Dan Akuntansi : EMBA, 2025)
In today's competitive era, universities must adopt strategies to improve the quality and value of the company. Employee performance and loyalty are important drivers for the sustainability of the company, and human resources (HR) play an important role in driving goals. This study aims to determine the effect of competence, work motivation, and work environment on employee job satisfaction at STEI Indonesia. This study uses an associative research strategy to determine the effect of three independent variables, namely Competence, Motivation, and Work Environment on Employee Job Satisfaction. This quantitative research is supported by a survey method based on positivism, using a questionnaire as a data collection tool. This study shows that competence does not directly increase job satisfaction. However, higher work motivation will result in higher job satisfaction. This study also highlights the significant impact of the work environment on job satisfaction. The better the work environment, the higher the job satisfaction. These findings provide valuable insights for institutions to understand the factors that influence employee job satisfaction and apply them to improve employee welfare and productivity